The genetic behavior of yield and its important components of some types of tomato (Solanum lycopersicum L.), Using (Line x Tester) analysis - خوجه حسان (Latakia University Journal -Biological Sciences Series, 2021)
The research conducted at Al-Jammaseh, Tartous in 2013 and 2014 seasons, studied the combining ability and gene action of parents and crosses for fruit productivity and its components using 8 hybrids in Line×tester fashion. Genotypes were evaluated in randomized block design with 3 replications. The ratio (σ2GCA/σ2SCA) and the degree of dominance indicated the superiority of additive gene actions over fruit weight and Pericarp thickness. The non-additive dominated productivity and fruit number. General Combining Ability showed L2 and T1 had the highest general combiners for productivity and fruit weight, L4 and T1 for number of fruits, and L3 and T2 for fruit Pericarp thickness. The hybrid (L4×T1) achieved significant superiority in productivity and number of fruits. Therefore, it can be certified after surpassing the strength of the standard hybrid. Lines contributed the largest percentage to the variation in the fruit weight, testers in pericarp thickness variations, while the hybrids in fruit number.